1994
DOI: 10.1007/bf00301682
|View full text |Cite
|
Sign up to set email alerts
|

Precision of dual x-ray absorptiometry and peripheral computed tomography using mobile densitometry units

Abstract: Irrespective of the method used for noninvasive bone mass determination, data comparison between different centers is a major problem as significant interunit variation may occur. We, therefore, have employed mobile densitometry units to reduce interunit variability in two large epidemiologic studies in Germany. Two cars were equipped with either two dual X-ray absorptiometry (DXA) instruments (QDR 1000 Hologic, USA) (car I) or a special purposed scanner for peripheral quantitative computed tomography (pQCT) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

1995
1995
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 16 publications
0
13
0
3
Order By: Relevance
“…Whereas available data indicate that the short-term reproducibility of these measurements is excellent (10,11), positioning is critical, and due to the variability of trabecular bone density throughout the metaphysis, any offset in the location to be scanned would significantly influence the values obtained (12). Additionally, the large range of metaphyseal morphology among subjects, diseases, and ages limits comparative cross-sectional studies and interpretation of the same scan location in longitudinal examinations (13).…”
Section: T He Development Of Precise Noninvasive Methodsmentioning
confidence: 99%
“…Whereas available data indicate that the short-term reproducibility of these measurements is excellent (10,11), positioning is critical, and due to the variability of trabecular bone density throughout the metaphysis, any offset in the location to be scanned would significantly influence the values obtained (12). Additionally, the large range of metaphyseal morphology among subjects, diseases, and ages limits comparative cross-sectional studies and interpretation of the same scan location in longitudinal examinations (13).…”
Section: T He Development Of Precise Noninvasive Methodsmentioning
confidence: 99%
“…The non significant differences among ROC-analyses showed that pQCT performed equally well in discrimation of fracture cases (hip and spine) as did all other densitometry techniques. Peripheral QCT there-G. Guglielmi et al: Quantitative CT at the skeleton S 37 [87] 0.8-1.5 SCT900 in vivo Hosie [67] 1.26 SCT900 in vivo Grampp [88] 0.9-2.1 XCT960 in vivo Hangartner [89] 0.57 Prototyp in vivo Hosie [67] 0.5 OSCAR in vivo Wapniarz [90] 0.9 XCT900 in vitro Guglielmi [91] 0 fore may be the method of choice when evaluating generalized bone loss [74]. The ROC curves for the pQCT are very similar to the recent results of Takagi et al [75].…”
Section: Clinical Evaluation Of the Pqct Technologymentioning
confidence: 99%
“…Peripheral quantitative computed tomography (pQCT) has been proposed as an adjunct to conventional densitometry [6,7]. BMD determination with pQCT at the site of the distal radius is a method of high precision and low radiation [8]. In addition, pQCT is the only noninvasive assessment of bone mineral to measure a true-dimensional density (as opposed to an areal density by standard methods) and to allow separate determination of cortical and trabecular bone density [9].…”
mentioning
confidence: 99%